IoT System of Medical Equipment Monitoring and Ambulance Tracking - Abdulmahdi, Mohammed; Ali, Ameer H.; Ali Abdul-Rahaim, Laith; Alhasani, Ahmed T. (International Conference on Engineering Technology and their Applications (Online), 2023)
With the rapid development in the field of information and communication technology, taking advantage of this development has become an urgent necessity in most areas such as the military, engineering, agriculture, and health life. The developers have provided an appropriate environment that accommodates most of these areas, which take on responsibility for looking for speed of implementation, speed of access, remote management, and other features that are in high demand and need. This paper introduces one of the important applications in the field of the Internet of Things (IoT) that is related to human life and health. a smart ambulance system implemented. Patient data collected by sensors are distributed in an ambulance and continuously received at the hospital side based on cloud computing, then it is sent to the specialists to give decisions, that may help to save critical cases according to the received information and it may need quick access and intervention by them Access to the patient shortens the time, especially during peak times. The ambulance tracking is done through the navigation monitoring system.